Mechanical properties and failure behaviour of architected alumina microlattices fabricated by stereolithography 3D printing. (15th April 2021) - Yap, Xiu Yun; Seetoh, Ian; Goh, Wei Liang; Ye, Pengcheng; Zhao, Yida; Du, Zehui; Lai, Chang Quan; Gan, Chee Lip
Highlights: Alumina microlattices with solid struts were fabricated with stereolithography 3D printing. Specific stiffness and specific strength of the microlattices were best for the Simple Cubic design, followed by Octet Truss and Kelvin Cell designs. Simple Cubic lattices failed column by column from the boundaries into the center while Octet Truss and Kelvin Cell lattices fractured along the diagonal (110) plane. At low relative densities, microlattice struts failed sequentially, due to truss buckling, while at high relative densities, the struts failed simultaneously. Because alumina has asymmetric strength in compression (2.3 GPa) and tension (0.3 GPa), fractures tend to initiate in localized regions of tension in the lattices, which developed despite the lattices being compressed globally. The alumina microlattices exhibited excellent moduli and strength for their mass densities and even demonstrated some degree of ductility (pseudoplastic strain 0.1% - 0.5%). Abstract: Alumina microlattices with solid struts and different topologies were fabricated by the stereolithography 3D printing method. Mechanical analysis shows that specific stiffness and strength were highest for Simple Cubic lattices, followed by Octet Truss, then Kelvin Cell lattices. The mechanical properties followed Ashby's power law well at small relative densities (≤ 0.3), but deviated from it at higher relative densities due to the increased importance of joint deformation. Failure in the Simple Cubic lattices proceeded in a column-by-column manner from the boundaries inwards to the centre, while fracture in Octet Truss and Kelvin Cell lattices took place predominantly along the diagonal (111) and (110) planes respectively. The underlying mechanism controlling these mechanical responses has been thoroughly discussed using finite element simulation analysis. Because lattice strength was limited by the tensile strength of alumina, which was an order of magnitude lower than its compressive strength, the microlattices were weaker than Ashby's predictions. Nevertheless, they were still able to exhibit better specific modulus and strength than many current engineering materials, as well as some degree of ductility in the form of pseudoplastic strains (0.1 % - 0.5 %). Graphical abstract: Image, graphical abstract